FBXO8 is a novel prognostic biomarker in different molecular subtypes of breast cancer and suppresses breast cancer progression by targeting c-MYC - Khan, Abdul Jamil; Man, Shad; Abbas, Manzar; Liu, Shihao; Zhang, Feng (Biochimica et biophysica acta. General subjects, 2024)
F-box only protein 8 (FBXO8) is a recently identified member of the F-box proteins, showcasing its novelty in this protein family. Extensive research has established FBXO8's role as a tumor suppressor in various cancers, including hepatocellular carcinoma, and colorectal cancer, Nevertheless, its functional, mechanistic, and prognostic roles in primary and metastatic breast cancer, particularly in different molecular subtypes of breast cancer, various stages, as well as its potential implications in immunotherapy, tumor microenvironment, and prognostic survival among breast cancer patients, remain unexplored. In this article, we employed a multi-dimensional investigation leveraging TCGA, TIMER, TISIDB, STRING, MEXPRESS, UALCAN, and cBioPortal databases to explore the underlying suppression mechanism of FBXO8 in breast cancer. FBXO8 negatively correlates with MYC, NOTCH, WNT and inflammatory signaling pathways in breast tumor microenvironment. Furthermore we conducted RT-PCR, western blot, cell proliferation, cell migration, and mRNA target gene RT-PCR analyses to elucidate the role of FBXO8 in breast cancer progression. Mechanistically, PTEN and FBXW7 expression were down-regulated and MYC, IL10, IL6, NOTCH1, WNT6 mRNA expressions were up-regulated in FBXO8 knockdown cell lines. c-MYC silenced cells showed an increase in FBXO8 protein level, which suggests a negative feedback loop between FBXO8 and c-MYC to control breast cancer metastasis. These findings illuminate the novel role of FBXO8 as a prognostic and therapeutic target across different molecular subtypes of breast cancer. Finally, through the utilization of virtual screening and Molecular Dynamics simulations, we successfully identified two FDA-approved medications, Ledipasvir and Paritaprevir, that demonstrated robust binding capabilities and interactions with FBXO8 •FBXO8 is lost in different molecular subtypes of breast cancer.•FBXO8 depletion promotes cell proliferation and cell migration.•FBXO8 depletion induces c-MYC protein expression.•FBXO8 depletion reduces PTEN and FBXW7 protein expressions.•FBXO8 negatively correlates with MYC, NOTCH, and WNT signaling pathways.